2022
DOI: 10.1126/sciadv.abm7322
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 prevents pathological vascular remodeling in atherosclerosis and abdominal aortic aneurysm

Abstract: Pathological vascular remodeling is the underlying cause of atherosclerosis and abdominal aortic aneurysm (AAA). Here, we analyzed the role of galectin-1 (Gal-1), a β-galactoside–binding protein, as a therapeutic target for atherosclerosis and AAA. Mice lacking Gal-1 ( Lgals1 −/− ) developed severe atherosclerosis induced by pAAV/D377Y-mPCSK9 adenovirus and displayed higher lipid levels and lower expression of contractile markers of vascular smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Galectin-1 (Gal-1) is a galactoside-binding protein that may serve as a new target for the treatment of atherosclerosis. Mice deficient in Gal-1 (Lgals1 −/− ) develop severe atherosclerosis with increased lipid levels in plaques and reduced expression of contractile markers in VSMCs compared to wild-type mice [ 36 ] ( Table 1 ). The plaque volume is reduced, intraplaque oxidized low-density lipoprotein (ox-LDL) was significantly reduced, and the phenotypic transformation of VSMCs was suppressed in plaque-prone apolipoprotein E and CRP4 double knockout (dKO) mice [ 37 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Galectin-1 (Gal-1) is a galactoside-binding protein that may serve as a new target for the treatment of atherosclerosis. Mice deficient in Gal-1 (Lgals1 −/− ) develop severe atherosclerosis with increased lipid levels in plaques and reduced expression of contractile markers in VSMCs compared to wild-type mice [ 36 ] ( Table 1 ). The plaque volume is reduced, intraplaque oxidized low-density lipoprotein (ox-LDL) was significantly reduced, and the phenotypic transformation of VSMCs was suppressed in plaque-prone apolipoprotein E and CRP4 double knockout (dKO) mice [ 37 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…In our previous study, macrophage NLRP3 inflammasome plays a significant role in promoting the progress of AAA ( 5 ). Furthermore, NLRP3 inflammasome activation regulates vascular smooth muscle cells phenotypic switch ( 49 ), which ultimately leads to AAA development through tunica medium elastin degradation ( 4 ). However, few studies have demonstrated the role and potential mechanism of FDX1 in AAA formation, which may become a promising research orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, lipid peroxidation exerts significant influence on cardiovascular diseases including atherosclerosis and AAA ( 2 , 3 ). Meanwhile, AAA is the late stage of atherosclerosis ( 4 ). Furthermore, inflammation has been demonstrated to play vital role in AAA pathology.…”
Section: Introductionmentioning
confidence: 99%
“…T hus, A LCA M physica l ly i nteracts wit h t he T cell-expressed scavenger receptor CD6, endothelial L1CAM, and galectin-8 (24). Notably, the other lectins, namely galectin-1 and galectin-3, have been reported to be associated with abdominal aortic aneurysms (26,27).…”
Section: Discussionmentioning
confidence: 99%